Luz, câmera, ciência: uma análise crítica da representação da ciência em filmes de ficção científica - Mattos, Celso Luiz (2018)
This work brings the analysis of the science representation of a group of cinematographic works of the genre of science fiction. Cinema, as a cultural manifestation, conveys values and visions of the world. It is possible to imagine situations, objects, beings and diverse worlds. But in every story there is the human being interacting in the universe of the film, and this interaction has much to say. Looking at Science and the scientific activity contained in a given film makes it possible to perceive how it is being represented and what values and worldviews associated with it, in evidencing it is possible to reflect and question it. Thus, a literature review was carried out on the importance and potential of cinema in education and science fiction for science teaching. With this study it was possible to propose analyzes of four works, Gravity (2013), Operation Big Hero (2014), Ex_Machina (2015) and Lost on Mars (2015). We used the analysis tool proposed by Piassi (2007) that allowed us to identify in the works the counterfactual elements and thematic poles in relation to science perceptible in the literary genre of science fiction. When analyzing the films, it was possible to note that the identification of counterfactual elements evidences scientific phenomena and concepts, while the identification of thematic poles makes it possible to establish relations between Science, Technology and Society. In addition, the analysis instrument used has the potential to be used as a methodology in science teaching for the analysis of science fiction films. The analyzes were made in order to discuss elements that could contribute with the planning of didactic activities for the teaching of sciences that counts on cinematographic works and with a critical vision on the scientific activity. Intending to this end, a science teaching that offers new meanings about science and technology in its relations with the social, political, economic and cultural context. This study is relevant for discussing ways of analyzing science fiction films with the aim of developing a critical view of science. This study can help broaden the eyes on the nature of science and the process of scientific research for both teachers and science education.